Association of Macroeconomic Factors With Nonrelapse Mortality After Allogeneic Hematopoietic Cell Transplantation for Adults With Acute Lymphoblastic Leukemia: An Analysis From the Acute Leukemia Working Party of the EBMT. (11th February 2016) - Giebel, Sebastian; Labopin, Myriam; Ibatici, Adalberto; Browne, Paul; Czerw, Tomasz; Socie, Gerard; Unal, Ali; Kyrcz-Krzemien, Slawomira; Bacigalupo, Andrea; Goker, Hakan; Potter, Mike; Furness, Caroline L.; et al.
Abstract: Purpose: From a global perspective, the rates of allogeneic hematopoietic cell transplantation (alloHCT) are closely related to the economic status of a country. However, a potential association with outcome has not yet been documented. The goal of this study was to evaluate effects of health care expenditure (HCE), Human Development Index (HDI), team density, and center experience on nonrelapse mortality (NRM) after HLA-matched sibling alloHCT for adults with acute lymphoblastic leukemia (ALL). Patients and Methods: A total of 983 patients treated with myeloablative alloHCT between 2004 and 2008 in 24 European countries were included. Results: In a univariate analysis, the probability of day 100 NRM was increased for countries with lower current HCE (8% vs. 3%; p = .06), countries with lower HDI (8% vs. 3%; p = .02), and centers with less experience (8% vs. 5%; p = .04). In addition, the overall NRM was increased for countries with lower current HCE (21% vs. 17%; p = .09) and HDI (21% vs. 16%; p = .03) and for centers with lower activity (21% vs. 16%; p = .07). In a multivariate analysis, the strongest predictive model for day 100 NRM included current HCE greater than the median (hazard ratio [HR], 0.39; p = .002). The overall NRM was mostly predicted by HDI greater than the median (HR, 0.65; p = .01). Both lower current HCE and HDI were associated with decreased probability of overall survival. Conclusion: Both macroeconomic factors and the socioeconomic status of a country strongly influence NRM after alloHCT for adults with ALL. Our findings should be considered when clinical studies in the field of alloHCT are interpreted. Abstract : Both macroeconomic factors and the socioeconomic status of a country strongly influence nonrelapse mortality after allogeneic hematopoietic cell transplantation (alloHCT) for adults with acute lymphoblastic leukemia. These findings should be considered when clinical studies in the field of alloHCT are interpreted.